Practical spectating: an exploration of the multiple roles of the intermedial performance audience - Swift, Elizabeth (International journal of performance arts and digital media, 2019)
The process of experiencing theatre is shifting from watching to doing. As genre-subverting performance work generates new modes of practical spectating, questions emerge about the evolution of the spectator and how we can reason about their role. This article is informed by developments in participatory and immersive theatre - but it focuses specifically on the spectator of intermedial performance and explores their relationship to work in which digital and live elements are conjoined. In exploring the roles of the spectator, the article examines the work of practitioners who use virtual reality (VR), immersive and surveillance technology and 3D film. I suggest that modes of reception, provoked by intermedial performance, merit specific forms of analysis, and I expound on how possible worlds theory and conceptual blending can be deployed in considering practical spectating. Borrowing terminology from digital theory the article explains how intermedial performance may be considered an ergodic artform. I look at how the experience of spectating takes on the quality of a personal journey, that may be at once emancipatory and restrictive, but which persistently provokes new questions about the production and reception of art.